2019
DOI: 10.1371/journal.pone.0217147
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of stroke in patients with HIV infection: A population-based study in Taiwan

Abstract: Background Few studies have evaluated whether people infected with human immunodeficiency virus (HIV) are at an increased risk of stroke in an Asian population. We investigated the association between HIV infection and the risk of developing stroke by age, calendar year of HIV diagnosis, and follow-up duration in Taiwan. Methods Using the claims data of a universal health insurance program, we identified 5,961 patients with HIV and 23,844 matched non-HIV subjects withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 39 publications
1
23
0
3
Order By: Relevance
“…In Europe, PLHIVs have a slightly lower stroke incidence than in the USA, consistent with lower rates seen in the general population of Europe compared to the USA (Vinikoor et al 2013;Corral et al 2009). More recent studies revealed a decline in the stroke risk among PLHIVs in recent years after the introduction of cART (Alvaro-Meca et al 2017;Lin et al 2019). There may be many reasons for this decline: adverse events associated with older antiretroviral regimens or more effective cART in the recent era, higher CD4+ T-cell nadir, lower frequency of opportunistic infections, and overestimated misdiagnoses due to limited diagnostic tests during the earlier period of the infection.…”
Section: Strokementioning
confidence: 56%
“…In Europe, PLHIVs have a slightly lower stroke incidence than in the USA, consistent with lower rates seen in the general population of Europe compared to the USA (Vinikoor et al 2013;Corral et al 2009). More recent studies revealed a decline in the stroke risk among PLHIVs in recent years after the introduction of cART (Alvaro-Meca et al 2017;Lin et al 2019). There may be many reasons for this decline: adverse events associated with older antiretroviral regimens or more effective cART in the recent era, higher CD4+ T-cell nadir, lower frequency of opportunistic infections, and overestimated misdiagnoses due to limited diagnostic tests during the earlier period of the infection.…”
Section: Strokementioning
confidence: 56%
“…Notably, although an increasing burden of morbidity and mortality due to stroke is likely as PWH age, ischemic stroke risk may be highest in younger PWH compared with age-matched controls. In a population-based study in Taiwan, HIV infection was associated with an elevated risk of developing any stroke (adjusted hazard ratio [AHR], 1.57; 95% CI, 1.15–2.14) and specifically ischemic stroke (AHR, 1.91; 95% CI, 1.25–2.91) in patients 45 years of age and younger, but no association was observed in older age groups [ 39 ]. While some data suggest that the newer INSTI-based regimens may be associated with a lower risk of ischemic stroke than older NNRTI- and PI-based regimens [ 40 ], our study population included only 8 participants (6.4%; 3 cases and 5 controls) with regimens including the first approved INSTI (ie, raltegravir), and our method of matching by regimen precluded analysis of regimen type as a predictor.…”
Section: Discussionmentioning
confidence: 99%
“…Результаты нейровизуализационных исследований у пациентов с ВИЧ-инфекцией и ГИ указывали Считается, что развитие сосудистых осложнений при ВИЧ-инфекции происходит преимущественно в более поздние стадии заболевания, и чем меньше уровень CD4-лимфоцитов, тем чаще у больных возникает инсульт [14,15]. Тем не менее имеются единичные работы, указывающие на высокий риск инсульта у ВИЧ-инфицированных лиц молодого возраста даже при достаточном уровне CD4-лимфоцитов с развитием инсульта через год после диагностирования ВИЧ-инфекции [8], что согласуется с нашими данными. У пациентов группы 1 в 3 субклинической стадии инсульт развился при достаточно высоком уровне CD4-лимфоцитов с диапазоном колебаний их уровня от 1540 до 504 кл./мкл.…”
Section: Opportunistic Diseases and Co-infections In Patients Withunclassified
“…На 1 января 2019 года общее количество зараженных ВИЧ составило 1,3 млн человек [3]. По частоте поражения органов и систем при ВИЧ-инфекции нервная система стоит на втором месте после иммунной системы [4], и на долю ОНМК приходится 1-5% всех поражений нервной системы [5][6][7][8][9]. Встречаемость инсультов у лиц моложе 45 лет со СПИДом в 10 раз выше, чем в общей популяции у лиц того же возраста [10].…”
unclassified